All-fiber coaxial Mach-Zehnder digital sensor - Celaschi, S.; Malheiros-Silveira, G. N. [UNESP]; Floridia, Claudio; Rosolem, J. B. (Optica Publishing Group, 2018)
We proposed a novel digital optical sensor designed from a tapered depressed-cladding fiber. The dynamic range is estimated 20 dB as its linear response for stresses up to 8 % of the elastic limit of the material.